DETECTION USE OF ARTIFICIAL INTELLIGENCE (AI) IN EDUCATIONAL ACTIVITIES - Ярова, Світлана; Заболотна, Ірина; Гензицька, Олена; Заболотный, Александр (SWorldJournal, 2024)
Taking into account the conditions of today, the introduction of information technologies in the educational process is urgent and relevant. In the presented work, the authors analyzed the possibilities, advantages and potential of using AI in higher educ